Fever Dreams: An Online Study - Schredl, Michael; Erlacher, Daniel (Frontiers in Psychology, 2020)
In addition to a large variety of somatic symptoms, fever also affects cognition, sleep, and mood. In an online survey with 164 participants, 100 fever dream reports were submitted. Fever dreams were more bizarre and more negatively toned and included more references to health and temperature perception compared to “normal” most recent dreams– findings that are in line with the continuity hypothesis of dreaming. Future studies should follow up this line of research by conducting diary studies during naturally occurring febrile illnesses and sleep laboratory studies with experimentally induced fever. It would also be very interesting to study the effect of thermal stimulation applied during sleep on dream content. This research helps to understand the subjective experiences while sleeping in an extreme condition (elevated body temperature).